Mutual Fund Shareholder Letters: Flows, Performance, and Managerial Behavior - Hillert, Alexander; Niessen-Ruenzi, Alexandra; Ruenzi, Stefan (Management Science, 2025)
Fund companies regularly send shareholder letters to their investors. We use textual analysis to investigate whether these letters’ writing style influences fund flows and whether it predicts performance and investment styles. Fund investors react to the tone and content of shareholder letters: a less negative tone leads to higher net flows. Thus, fund companies can use shareholder letters as a tactical instrument to influence flows. However, at the same time, a dishonest communication that is not consistent with the fund’s actual performance decreases flows. A positive writing style predicts higher idiosyncratic risk as well as more style bets, whereas there is no consistent predictive power for future performance. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The internet appendix and data files are available at https://doi.org/10.1287/mnsc.2021.03417 .